Evaluasi Penambahan Lapisan Menggunakan Metode SSD (Sliding Sleeve Door) Pada Sumur “RG-3” Lapangan “NR” - Nugroho Marsiyanto; Aulia Huda Panindita; Diah Ayu Kusuma Ningrum (Jurnal Bhara Petro Energi, 2024)
In the "RG-3" Well there are 3 production zones in one wellbore, UA-10, UA-11, and UA-12. The zone produced only UA-10 from 2015 until it experienced a decline in production in 2021 with the latest production reading reaching 3 MMscfd. So efforts need to be made to increase production by doing a good job by opening new zones or existing zones in the well. The "RG-3" well carried out work on adding zone layers by opening the pre-existing UA-12 zone with the hope that the UA-12 zone could increase gas production results. The well intervention work process for adding this layer uses a slickline unit with the open SSD method. The “RG-3” gas well in the "NR" field is located in the Arang Formation layer. The data required in this research is gas production data, work cost data, and other supporting data. In the economic evaluation of adding layers using the SSD method, with a work process of up to 13 days by calculating POT, NPV, and ROR the results reached POT 3 days, NPV = US$ 85.147, and ROR reached 1.007% with the assumption The production results obtained were 8 MMscfd.